Advanced Deep Learning with R: Become an Expert at Designing, Building, and Improving Advanced Neural Network Models Using R - Rai, Bharatendra (Packt Publishing, Limited, 2019)
This book will help readers to apply deep learning algorithms in R using advanced examples. You will cover variants of neural network models such as ANN, CNN, RNN, LSTM, and more using expert techniques. Readers will make use of popular deep learning libraries such as Keras-R, Tensorflow-R, and more to implement AI models.